Laminated film and its manufacturing method and use method
Laminated films using isoprene block copolymers with varying vulcanization systems address the issues of strength and allergic reactions in synthetic latex, providing chemical resistance and skin compatibility.
Patent Information
- Application Number
- JP2021521508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-17
- Filing Date
- 2019-11-18
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2039-11-18
AI Technical Summary
Existing synthetic latex materials lack the necessary strength, chemical resistance, and compatibility for specific applications, particularly those requiring contact with sensitive skin, while natural rubber latex can cause allergic reactions.
A method involving the formation of laminated films using isoprene block copolymers, where one layer contains a vulcanization system and the other does not, with specific compositions and curing processes to achieve desired properties.
The laminated films exhibit excellent physical characteristics, including resistance to chemicals and compatibility with sensitive skin, while minimizing allergic reactions.
Smart Images

Figure 0007627212000001 
Figure 0007627212000002
Abstract
Description
[Technical field]
[0001] This application claims priority from U.S. Patent Application No. 62 / 780,373, filed December 17, 2018, the disclosure of which is incorporated herein by reference.
[0002] The present disclosure relates to methods for making laminate articles and films comprising isoprene block copolymers. [Background technology]
[0003] Natural rubber latex has been applied for many years as a material for manufacturing gloves and condoms. Although the physical properties of cured natural rubber make it an excellent choice for such applications, natural rubber latex does present a risk of allergic reaction. Type I hypersensitivity can occur in response to proteins present in natural rubber latex.
[0004] Synthetic materials have been developed that avoid the Type I skin sensitivity and allergy problems associated with natural rubber, such as synthetic polyisoprene and latex made from synthetic polyisoprene for use in thin film articles such as gloves and condoms. In embodiments for making articles from natural or synthetic latex, the synthetic isoprene polymer is converted to a more durable material by vulcanization with the addition of a curing system, e.g., sulfur, an activator / accelerator system. In the process, a component in the shape of an article is immersed in a latex precompound containing the curing system, and then the latex is cured on the component.
[0005] Synthetic materials have been introduced that do not contain vulcanizing / accelerating products and do not require crosslinking. Some of them offer the softness and flexibility of natural rubber, but do not have the resistance to certain types of chemicals for certain applications.
[0006] There remains a need for improved methods for producing rubber latex articles having the necessary properties for strength, chemical resistance, and suitability for specific applications. Summary of the Invention
[0007] In one embodiment, a method for forming a dip-molded article is disclosed, which includes providing a mold for forming a dip-molded article, immersing the mold in a first latex composition containing a vulcanizing agent component selected from sulfur, an organic peroxide, a vulcanization activator, a vulcanization accelerator, and a mixture thereof to form a first layer, immersing the mold with the first layer formed thereon in a second latex composition not containing a vulcanizing agent component to form a laminate film with the second layer formed on the first layer, heating to a temperature between 90 and 140°C to cure the laminate film, and removing the laminate film from the mold by inversion so that the second layer is on the inside and the first layer is on the outside.
[0008] In some embodiments, the first latex composition and the second latex composition are prepared from the same synthetic isoprene block copolymer. In other embodiments, the first latex composition and the second latex composition are based on different polymers, the first latex composition containing one of a synthetic polyisoprene polymer latex, a nitrile-based copolymer latex, a synthetic isoprene polymer grafted with a monomer having a carboxyl group, a natural rubber latex, a polychloroprene latex, a carboxylated acrylonitrile butadiene latex, a polyurethane latex, or a styrene-butadiene latex. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following terms are used throughout the specification and have the following meanings, unless stated otherwise.
[0010] "Molecular weight" (or MW) in the context of copolymers refers to the true molecular weight, expressed in g / mol, of a polymer or block of copolymer, which can be measured by gel permeation chromatography (GPC) using polystyrene calibration standards according to ASTM 5296-11, and which represents the molecular weight at the peak of the distribution. The calibrated MW is the styrene equivalent MW, also called the apparent MW. The styrene equivalent molecular weight can be converted to the true molecular weight if the styrene content of the polymer and the vinyl content of the diene segments are known.
[0011] "Coupling efficiency" is defined as the number of molecules of coupled polymer divided by the number of molecules of coupled polymer plus the number of molecules of uncoupled polymer. Coupling efficiency can be determined theoretically from the stoichiometric amount of coupling agent required for complete coupling, or coupling efficiency can be determined by analytical methods such as GPC. For example, if the coupling efficiency of a block copolymer is 80%, the copolymer will contain 20% diblock and 80% triblock and multiarm blocks.
[0012] In embodiments, laminate articles with superior physical properties are made from layers formed from latexes of different compositions, with and without crosslinking systems that include ingredients such as sulfur, organic peroxides, activators, etc. After curing, the article is inverted so that the layers without the vulcanization system are on the inside and the layers with the vulcanization system are on the outside, e.g., for contact with sensitive skin.
[0013] Synthetic Isoprene Block Copolymers: The first step in the synthesis of isoprene block copolymers involves contacting an alkenyl arene with an initiator, typically an organolithium compound, in the presence of an inert diluent, thereby forming a living polymeric compound having the simple structure A-Li. Thus, A is composed of at least 90 mole % of the alkenyl arene. The alkenyl arene is preferably styrene. Other useful alkenyl arenes from which the A block can be formed include alpha methyl styrene, tert butyl styrene, vinyl piperidine and other cyclic alkylated styrenes and mixtures thereof. Small amounts of other anionically copolymerizable monomers can be included. The living polymer in solution is then contacted with isoprene to form a polymer block B. Other copolymerizable monomers may also be included. B is composed of at least 90 mole % isoprene. The resulting living polymer has the simple structure AB-Li. It is at this point that the living polymer can be coupled by the addition of a multifunctional coupling agent or a second amount of alkenyl arene can be added to form a linear block copolymer ABA.
[0014] In one embodiment, the block copolymer comprises at least two blocks (A) of polymerized monoalkenyl arenes and at least one block (B) of polymerized conjugated dienes, the blocks being ABA or ABY-(BA). n where Y represents the residue of a coupling agent and n+1 represents the average number of arms in the radial structure. In embodiments, the coupling efficiency is greater than 90%, alternatively 92%-100%. Exemplary coupling agents include, but are not limited to, polyepoxides, polyisocyanates, polyimines, polyaldehydes, polyketones, polyanhydrides, polyesters, polyhalides, and compounds containing two or more functional groups, such as epoxy and aldehyde groups, isocyanate and halide groups. In one aspect, the coupling agent is γ-glycidoxy-propyl-trimethoxy-silane (GPTS).
[0015] In some embodiments, the diblock arms are coupled together to form a triblock copolymer when (n+1) is equal to 2 (meaning that the arms of two diblocks are coupled together), or a radial polymer when (n+1) is greater than 2.
[0016] The A block is formed by polymerization of a monoalkenyl arene monomer. The mono-alkenyl arene can be styrene, α-methylstyrene, methylstyrene other than α-methylstyrene, vinyltoluene, para-butylstyrene, ethylstyrene, and vinylnaphthalene, which can be used alone or in combination of two or more. In one embodiment, the monoalkenyl arene is styrene.
[0017] The B block is a polymer block of a conjugated diene and has rubber-like properties. The conjugated diene can be 1,3-butadiene, a substituted butadiene such as isoprene, piperylene, 2,3-dimethyl-1,3-butadiene, myrcene, and 1-phenyl-1,3-butadiene, or a mixture thereof. In one embodiment, B is isoprene.
[0018] In the radial structure AB embodiment, the living diblock arms are first formed by sequential anionic polymerization and then coupled using a coupling agent having a functionality of 3 or more. In the radial block copolymer structure, the A blocks have an average molecular weight between 10,000 g / mol and 12,000 g / mol. The B blocks have an average molecular weight between 75,000 g / mol and 150,000 g / mol, alternatively between 80,000 g / mol and 120,000 g / mol. The weight percentage of the A blocks in the finished block polymer is between 8 and 15%, alternatively between 10 and 12% by weight.
[0019] When the block copolymer is a linear polymer, the ABA structure can be formed by linear step-growth polymerization or by coupling of living AB arms. In these linear block copolymers, each A block has a molecular weight of 8,000 g / mol to 15,000 g / mol, alternatively 9,000 g / mol to 14,000 g / mol. The total molecular weight of the block copolymer is 150,000 g / mol to 250,000 g / mol, alternatively 170,000 g / mol to 220,000 g / mol. The block copolymer has a monoalkenyl arene content of 8 wt% to 15 wt%, alternatively 9 wt% to 14 wt%, based on the total weight of the block copolymer.
[0020] In one embodiment for use with a vulcanizing agent-free layer, the copolymer is a SIS (styrene-isoprene-styrene) block copolymer containing 18% styrene and 82% isoprene and having a weight average molecular weight of about 130,000 Daltons. In another embodiment for use with a vulcanizing agent-free layer, the copolymer has the formula AB-Ym-(BA) n wherein A, B, Y, and n are as defined above, A has a weight average molecular weight of 8,000 to about 15,000 daltons, B has a weight average molecular weight of about 30,000 to about 200,000 daltons, m is 0 or 1, and n is an integer from 1 to 5.
[0021] In yet another embodiment for use with a layer without a vulcanizing agent, the copolymer is a mixture comprising 60% to 10% by weight of a radial styrene block copolymer and 40% to 90% by weight of a styrene-diene diblock copolymer. The styrene-diene diblock copolymer is a styrene-isoprene diblock copolymer and / or a styrene-butadiene diblock copolymer. When the diblock copolymer is a styrene-butadiene diblock copolymer, it has a styrene content of 10% to 30% by weight.
[0022] In an embodiment, the synthetic isoprene polymer has a Mooney viscosity [ML 1+4, 100°C].
[0023] Synthetic isoprene polymers can be prepared in any suitable manner, for example, by polymerization with Ziegler-Natta coordination type catalysts such as titanium or neodymium, using anionic polymerization methods using organolithium compounds as initiators in inert solvents to directly produce synthetic polyisoprene latex, or by emulsion or suspension polymerization of isoprene. The synthetic isoprene polymers are optionally copolymerized with ethylenically unsaturated monomers.
[0024] <Latex>: In embodiments, where the polymer is not directly produced in the final form of a latex, a latex emulsion is formed by emulsifying a solution or fine suspension of a synthetic polymer dissolved or finely dispersed in an organic solvent in the presence of a surfactant in water, and optionally removing the organic solvent, thereby producing a synthetic polymer latex.
[0025] The latex emulsion is characterized by a solids content of 20 weight percent (wt%) to 80 wt%, alternatively 30 wt% to 70 wt%, alternatively 35 wt% to 65 wt%, a surfactant content of 0.5 to 50 parts by weight per 100 parts by weight of synthetic polyisoprene, and a water content of 50 to 5000 parts by weight per 100 parts by weight of synthetic polymer. Anionic, cationic or nonionic surfactants or combinations thereof can be used as surfactants.
[0026] The latex emulsion may further include additives such as antioxidants, e.g., primary antioxidants, secondary antioxidants, and carbon radical scavengers. Other additives may include pH adjusters, defoamers, preservatives, crosslinkers, chelating agents, oxygen scavengers, dispersants, oils, cosolvents, waxes, colorants, tackifiers, fillers, release agents, antiblocking agents, and other additives. pH adjusters include, for example, sodium hydroxide, potassium hydroxide, and other hydroxides of alkali metals, sodium carbonate, potassium carbonate, and other carbonates of alkali metals, sodium bicarbonate and other bicarbonates of alkali metals, ammonia, trimethylammonium, triethanolamine, and other organic amine compounds. The primary antioxidant may be added in an amount of 0.3% to 1.5% by weight, or 0.5% to 1% by weight, based on the total weight of the latex emulsion. Also, the secondary antioxidant may be used together with the primary antioxidant in an amount ranging from 0.5% to 2.5% by weight, or 0.5% to 2% by weight.
[0027] In some embodiments, and depending on the layer, the latex does not include any crosslinking additives (e.g., vulcanizing agents or accelerators), and in other embodiments for use with a particular layer, the latex includes a crosslinking additive.
[0028] In an embodiment, the latex is characterized in having a volume average particle size of 0.5 to 10 μm, or 0.5 to 3 μm, or 0.5 to 2 μm.
[0029] Sulfur-based crosslinking agents (vulcanizing agents): In the embodiment where the latex is cured with a vulcanizing crosslinking agent, the latex emulsion is cured with sulfur, which can be in many forms, such as powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur, sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, N,N'-dithio-bis(hexahydro-2H-azenopine-2), phosphorus-containing polysulfides, high molecular weight polysulfides, 2-(4'-morpholinodithio)benzothiazole, and other sulfur-containing compounds. These sulfur-based vulcanizing agents can be used alone as a single type or two or more types can be used together.
[0030] The amount of sulfur ranges from 0.05 to 10 parts by weight, or 0.1 to 3 parts by weight, per 100 parts by weight of synthetic polymer, or 0.2% to 0.5% by weight based on the total weight of the latex emulsion.
[0031] Peroxide-Based Crosslinkers: In embodiments, the curing of the latex emulsion can be carried out using organic peroxides and conditions commonly used in the curing of natural and synthetic polydiene rubbers. The organic peroxide can be added to the latex emulsion to produce crosslinks between the unsaturated bonds in the rubber chains of the B block. In one embodiment, the organic peroxide is added to the latex emulsion in the form of an aqueous dispersion. The concentration of peroxide in the reaction is provided in an amount ranging from 20 ppm to 80 ppm, alternatively from 20 ppm to 60 ppm, and further alternatively from 30 ppm to 60 ppm, in terms of active oxygen in parts per million (ppm).
[0032] Examples of organic peroxides include, without limitation, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxyketals, ketone peroxides, peroxyketal diacyl peroxides, peroxydicarbonates, monoperoxycarbonates, peroxyesters, dialkylbenzoyl peroxides, lauroyl peroxide, t-butyl peroxybenzoate, 1,1-di-t-butylperoxy-2,4-di-t-butylcyclohexane, succinic acid peroxide, benzoyl peroxide, t-butylperoxy-2-ethylhexanoate, p-chlorobenzoyl peroxide, t-butylperoxyisobutyrate, t-butylperoxyisopropylcaprylate, and the like. Examples of the peroxyalkylene oxide include tert-butyl peroxycarbonate, t-butyl peroxylaurate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxyacetate, di-t-butyl peroxyphthalate, t-butyl peroxymaleic acid, cyclohexanone peroxide, t-butyl peroxybenzoate, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butyl-peroxy)hexane, t-butyl cumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3,α,α'-bis-t-butylperoxy-1,4-diisopropylbenzene, or combinations thereof.
[0033] In one embodiment, the peroxide crosslinking formulation includes at least one peroxide and at least one compound having a secondary amine group selected from an amino acid such as arginine, folic acid, and a polyethyleneamine, as disclosed in US20170355785A1, which is incorporated herein by reference.
[0034] <Vulcanization accelerator>: In an embodiment in which the latex is used with a vulcanizing agent, such as sulfur, the vulcanization (vulcanization or vulcanizing) accelerator can be used in an amount of 0.05 to 5 parts by weight, more preferably 0.1 to 2 parts by weight, relative to 100 parts by weight of the synthetic polymer. Examples include diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid, and other dithiocarbamic acids and their zinc salts, 2-mercaptobenzothiazole, zinc 2-mercaptobenzothiazole, 2-mercaptothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthiocarbarylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholinodithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 1,3-bis(2-benzothiazylmercaptomethyl)urea.
[0035] In some embodiments, the enhancer is selected from compositions with reduced allergenic potential, e.g., transient xanthate enhancers selected from diisopropyl xanthogen polysulfides, dibutyl xanthogen disulfide, and diisopropyl xanthogen disulfide, as disclosed in US9550906B2, incorporated herein by reference.
[0036] <Vulcanization activator>: Depending on the vulcanization activator, in some embodiments, a vulcanization activator can be used. The activator can also function as an accelerator. Examples of activators include, but are not limited to, zinc oxide, lead monoxide, zinc salts, and combinations thereof.
[0037] <Method of Forming Articles>: To prepare thin-walled rubber articles, layers are formed from latex prepared from polymer(s), where at least one layer has a crosslinking component (e.g., sulfur, peroxide, accelerator, activator, etc.) and at least one layer does not contain a crosslinking system. The various layers can be prepared from the same or different polymer latex compositions to form a laminated membrane.
[0038] Thin-walled rubber articles or films refer to all forms, whether produced by painting and evaporation or by dipping. In one aspect, latex films are formed by the "coalescence" of individual latex particles, which are normally held apart by stabilizing forces such as electrostatic and / or charged polymer chain end groups or steric forces resulting from adsorbed surfactants and polymers, with compression, deformation, aggregation and polymer chain interdiffusion. These forces and other forces resisting particle deformation can be overcome by evaporation of the continuous phase, i.e., water present in the emulsion. The formation of a transparent, crack-free continuous film depends on the minimum film-forming temperature (MFFT) of the polymer, judged visually on a bar with a temperature gradient, which in turn depends on the modulus of elasticity of the film-forming material, resistance to particle deformation, and, to a lesser extent, the viscosity of the polymer.
[0039] In the process, a suitable surface is coated with a latex containing a crosslinker and / or accelerator system to form a first layer, and then an additional layer without crosslinker (and / or accelerator) is formed or laminated thereon. The resulting film is dried and crosslinked at drying and curing temperatures that vary from 25 to 130°C. Depending on the application, if the article formed is for contact with sensitive skin, the molded article is inverted so that the layer formed from the latex without crosslinker (and / or accelerator) is on the inside and the other layer (prepared from a latex with crosslinker and / or accelerator) is for the outside.
[0040] In one example for making thin-walled articles, a mold (former) is first dipped into a latex that does not contain a crosslinker (and / or accelerator). The dip-coated mold is then removed from the latex and allowed to dry (air). The mold can be dip-coated multiple times with the same latex before being dip-coated with a different latex (containing a crosslinker and / or accelerator). After the mold is dip-coated with the first latex and dried, it is dip-coated with a second latex containing a crosslinker system and allowed to dry, etc. The mold can be dip-coated multiple times with latex containing a crosslinker.
[0041] In some embodiments, a coagulant can be used before immersing the mold in the dip-forming latex composition or after removing the mold from the dip-forming latex. Examples of coagulants include barium chloride, calcium chloride, magnesium chloride, zinc chloride, aluminum chloride, or other metal halides, barium nitrate, calcium nitrate, zinc nitrate, or other nitrates, barium acetate, calcium acetate, zinc acetate, or other acetates, calcium sulfate, magnesium sulfate, aluminum sulfate, or other sulfates, or other water-soluble polyvalent metal salts, and mixtures. In one example, the mold is immersed in a dispersion of the coagulant, the coagulant on the surface of the mold is dried, and then the mold is immersed in the rubber latex.
[0042] After the various layers are formed, a film (or article) having the stacked layers is formed and then the film can be cured by heating it to less than 90° C. to 130° C., or up to 110° C. to 125° C. In one example, curing is at 110-140° C. for 10-40 minutes.
[0043] In one embodiment of the method of using the latex composition using an organic peroxide as a curing system, the latex film comprises (i) a first layer of a conjugated diene-containing polymer, an organic peroxide, and optionally sulfur, and (ii) a second layer comprising a styrenic block copolymer that does not contain an organic peroxide. The sulfur added to the first peroxide-containing latex acts as an oxygen scavenger. Dissolved and atmospheric oxygen are removed from the first layer prepared from the conjugated diene-containing polymer latex cured in this manner, providing a strong and elastic film.
[0044] As disclosed herein, the method and latex composition are for use with synthetic isoprene polymers, although other compositions can be used, such as nitrile-based copolymer latexes, synthetic isoprene polymers grafted with monomers having carboxyl groups for improved properties, natural rubber latex, polychloroprene, carboxylated acrylonitrile butadiene, polyurethane, styrene-butadiene, and the like. Additionally, the latex layer that contacts the skin can include additives suitable for the particular application, such as cannabis or cannabis-derived compositions for enhanced skin sensation. In other embodiments, the latex layer that contacts the skin (or outer layer) can include additives for a visually noticeable color change upon a break or soiling event. In some embodiments, after inversion of the layers, the formed article can undergo further processing, such as coating for additional strength / protection / donning, or coating with antimicrobial agent(s) for antiblocking properties.
[0045] <Applications>: The formed articles are characterized by excellent adhesion between different layers, with little if any peeling, and can be used as membranes, balloons, surgical gloves, examination gloves, electrical insulating gloves, industrial gloves, or condoms. In applications involving contact with sensitive skin, the layer formed from latex without vulcanizing agents (and / or accelerators) is in contact with the skin, and the other layer (prepared from latex with vulcanizing agents) is for the outside, having properties such as chemical resistance. EXAMPLES
[0046] EXAMPLES: The following illustrative examples are intended to be non-limiting.
[0047] A latex was prepared using Polymer 1, a radial block copolymer with an A block composed of polymerized styrene monomers and a B block composed of polymerized isoprene monomers. The molecular weight of the A block was 11,800, the molecular weight of the B block was 96,000, the coupling agent was γ-glycidoxy-propyl-trimethoxy-silane (GPTS), and the average number of arms (n) was 2.7.
[0048] The latex was diluted to 30-35% solids and 0.3 parts by weight of Manawet 172 surfactant was added. The pH was raised to 11 by the addition of a 10% KOH solution. The organic peroxide dispersion was added to the latex and the mixture was stirred for at least 24 hours.
[0049] To obtain thin-walled immersions, a metal plate (12 x 4.5 cm) was used. The components were heated in an oven at 100 °C and then immersed in the coagulation liquid for 30 seconds. The components were dried in the same oven at 100 °C for at least 90 seconds and then immersed in the composite latex dispersion (20-30 seconds). Immediately after immersion, the wet latex film was coagulated at 100 °C for 48 seconds, followed by a leaching step in a water bath at 50 °C for 5 minutes. The film was cured at 120 °C for 20 minutes. The film was dusted with silica powder and removed from the components.
[0050] The swelling of the material was measured by cutting a circular piece of membrane with a diameter of 15 mm, placing it in toluene in a Petri disc and measuring the diameter of the swollen membrane after 1 hour.
[0051] Example 1: A latex containing Polymer 1 was compounded with 0.5 parts by weight of Perkadox L-W40, an aqueous dispersion of dibenzyl peroxide, and 0.25 parts by weight of a sulfur dispersion.
[0052] Example 2: A latex containing Polymer 1 was compounded with 1 part by weight of Perkadox L-W40, an aqueous dispersion of dibenzyl peroxide, and 0.5 parts by weight of a sulfur dispersion.
[0053] Comparative Laminate Structure 1: A latex containing Polymer 1 was compounded with 0.5 parts by weight of Perkadox L-W40, an aqueous dispersion of dibenzyl peroxide, and no sulfur dispersion was added.
[0054] Comparative Laminate Structure 2: A latex containing Polymer 1 was compounded with 1 part by weight of Perkadox L-W40, an aqueous dispersion of dibenzyl peroxide, with no added sulfur dispersion. The oven was purged with nitrogen to remove atmospheric oxygen.
[0055] [Table 1]
[0056] Example 3: A glove is prepared with a first layer containing a first latex with a vulcanization system with sulfur and an accelerator as disclosed in US8673172 ("old latex"), and a second layer containing a second latex without a crosslinking material with an accelerator as disclosed in US20150104663 ("new latex"). The new latex without accelerator is laminated on the old latex layer according to the following method: 1. Coagulant dripping, 2. Drying, 3) Old latex compound immersion, 4) Drying at 100°C for 1 minute, 5) New latex without accelerator immersion, 6) Drying at 100°C for 1 minute, 7) Washing at 50°C for 5 minutes, 8) Curing at 130°C for 25 minutes.
[0057] After immersion and temperature treatment, the glove is inverted so that the new latex layer is on the inside and in contact with the skin. The resulting article has the following properties: Note that the finished product shows no delamination and minimal expansion under stress.
[0058] [Table 2]
[0059] For purposes of this specification and claims, unless otherwise indicated, all numbers expressing quantities, percentages or ratios, and other numerical values used in the specification and claims are to be understood in all instances as modified by the term "about." Thus, unless expressly stated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending on the desired properties sought. As used in this specification and appended claims, the singular forms "a," "an," and "the" include plural referents unless expressly and explicitly limited to one referent. As used herein, the term "include" and grammatical variations thereof are intended to be non-limiting, and the description of items in a list does not exclude other similar items that may substitute for or be added to the listed items. As used herein, the term "comprising" means including the identified elements or steps following the term, but any such elements or steps are not exhaustive and embodiments may include other elements or steps. Although the terms "comprising" and "including" have been used herein to describe various embodiments, the terms "consisting essentially of" and "consisting of" can be used in place of "comprising" and "including" to provide more specific embodiments of the disclosure and are disclosed.
[0060] Unless otherwise specified, the description of a genus of an element, material or other component from which individual components or mixtures of components may be selected is intended to include all possible sub-inclusive combinations of the listed components and mixtures thereof.
[0061] The patentable scope is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that are no different from those literally recited in the claims, or if they contain equivalent structural elements that are no different from those literally recited in the claims. All references mentioned in this specification are incorporated herein by reference to the extent not inconsistent herewith.
Claims
1. 1. A method for forming a dip-molded article, comprising: Providing a mold for forming a dip-molded article; dipping the mold into a first latex composition comprising a crosslinker component selected from sulfur, an organic peroxide, a vulcanization activator, a vulcanization accelerator, and mixtures thereof to form a first layer; immersing the mold having the first layer formed thereon into a second latex composition not containing a crosslinking agent component to form a laminated film having the second layer formed on the first layer; Curing the laminated film by heating to a temperature between 90° C. and 140° C.; removing the laminated film from the mold by inverting the film so that the second layer is on the inside and the first layer is on the outside; the first latex composition and the second latex composition are prepared from the same synthetic isoprene block copolymer; The synthetic isoprene block copolymer has the general formula A-B-A or A-B-Y-(B-A) n wherein n ranges from 1 to 6 and n is related to the average number of arms in the coupled polymer (N) by the formula N=n+1; Y represents the residue of a coupling agent; A is formed by polymerization of mono-alkenyl arene monomers selected from styrene, α-methylstyrene, methylstyrene other than α-methylstyrene, vinyl toluene, para-butylstyrene, ethylstyrene, and vinyl naphthalene; and B is a polymer block of a conjugated diene selected from 1,3-butadiene, isoprene, piperylene, 2,3-dimethyl-1,3-butadiene, substituted butadienes such as myrcene and 1-phenyl-1,3-butadiene, or mixtures thereof.
2. The method of claim 1 , wherein the first latex composition comprises sulfur and an organic peroxide.
3. 3. The method of claim 1 or 2, wherein the organic peroxide is selected from the group consisting of hydroperoxides, dialkyl peroxides, peroxyesters, diaryl peroxides, diacyl peroxides, ketone peroxides, peroxydicarbonates, and peroxyketals.
4. 3. The method of claim 1 or 2, wherein the monoalkenyl arene is styrene and the conjugated diene is isoprene.
5. The method according to claim 1 or 2, wherein the coupling agent is γ-glycidoxy-propyl-trimethoxy-silane.
6. The method of claim 1 or 2, wherein the pH of the second latex composition is 10 or greater.
7. 3. An article prepared by the method of claim 1 or 2 which is a membrane, a balloon, a surgical glove, an examination glove, an electrical insulating glove, an industrial glove or a condom.
8. A laminate article comprising at least two layers: a first layer comprising a first latex composition containing at least a crosslinker component selected from sulfur, an organic peroxide, a vulcanization activator, and a vulcanization accelerator; A second layer comprising a second latex composition that does not include a crosslinker component. and the laminate article comprises: dipping a form having the shape of a laminate article into a first latex to form a first layer; dipping the mold having the first layer formed thereon into a second latex composition to form a laminate article having a second layer on the first layer; Heat to a temperature between 90-140° C. to cure the laminate article; Inverting the laminate so that the second layer is on the inside and the first layer is on the outside. is formed by the first latex composition and the second latex composition are prepared from the same synthetic isoprene block copolymer; The synthetic isoprene block copolymer has the general formula A-B-A or A-B-Y-(B-A) n wherein n ranges from 1 to 6 and n is related to the average number of arms in the coupled polymer (N) by the formula N=n+1; Y represents the residue of a coupling agent; A is formed by polymerization of a mono-alkenyl arene monomer selected from styrene, alpha-methylstyrene, methylstyrene other than alpha-methylstyrene, vinyl toluene, para-butylstyrene, ethylstyrene, and vinyl naphthalene; and B is a polymer block of a conjugated diene selected from 1,3-butadiene, isoprene, piperylene, 2,3-dimethyl-1,3-butadiene, substituted butadienes such as myrcene and 1-phenyl-1,3-butadiene, or mixtures thereof.
9. 9. The laminate article of claim 8, wherein the first latex composition comprises sulfur or an organic peroxide as a crosslinking agent.
Citation Information
Patent Citations
Gloves made of low allergic natural rubber and its manufacturing method
JP2002120243A
Thin wall rubber vulcanizates derived from unaccelerated latex
JP2006502024A
Dip molding composition, and dip molded product
JP2012062487A
Olefinically unsaturated radial styrenic block copolymer and improved latex free of vulcanizing agents
JP2016538360A